Dealing with problem employees : how to manage performance & personality issues in the workplace - DelPo, Amy, 1967-; Guerin, Lisa, 1964- (Nolo, 2024)
"This book tells business owners, managers, and supervisors everything they need to know about how to identify difficult employees, how to manage them during the employment relationship, and how to terminate them in a way that reduces the company's legal risk of a wrongful termination lawsuit. It will give them the confidence to deal with problem employees directly and make the tough decision to terminate when it's clear that the situation isn't improving. With legal and practical information you need to handle all kinds of issues. Includes sample policies, forms, and checklists." --